Evaluation of the implementation of the safewards model within inpatient mental health services in West Nusa Tenggara, Indonesia - Nita Sudiarsini; Saimi Saimi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The safewards model of psychiatric care is an approach developed to improve the safety and quality of care in psychiatric wards. this approach aims to reduce incidents of violence, improve therapeutic relationships between patients and healthcare workers, and create a safer inpatient environment and support patient recovery. Purpose: To analyze the evaluation of the implementation of the safewards inpatient model in mental hospitals. Method: Qualitative research with explorative descriptive design. Data and information sources come from 15 informants consisting of: hospital management (A-1), head of nursing (A-2), head of education and training (A-3), head of medical services (A-4), head of nursing (A-5), head of facilities (A-6), head of finance (A-7), implementing doctors (B-8, B-9), implementing nurses (C-10, C-11, C-12, C-13, C-14, C-15). To obtain complete information, in-depth interviews and focus group discussions (FGD) were conducted with informants. Furthermore, thematic, narrative, inductive, and explanatory data analysis were carried out, then reduction and triangulation were carried out. Results: The implementation of the safewards model with 10 intervention strategies has been proven effective in mental health services. In addition, the implementation of this intervention has been proven effective in reducing conflict, improving therapeutic communication, and accelerating the patient's recovery process. With the right strategy, this model can be increasingly integrated into the mental health service system that is oriented towards patient recovery and well-being. Conclusion: The implementation of the safewards model is effective in mental health services. Although there are still various challenges, such as limited professional human resources and other supporting facilities and infrastructure, the high commitment of health workers and management is a key factor in ensuring the sustainability of this program.